2019
DOI: 10.1186/s41239-019-0156-z
|View full text |Cite
|
Sign up to set email alerts
|

Using Hypervideo to support undergraduate students’ reflection on work practices: a qualitative study

Abstract: According to several exploratory studies, the HyperVideo seems to be particularly useful in highlighting the existing connections between the school-based and the work-based contexts, between authentic work situations and theoretical underpinnings. This tool and its features, in particular, the video annotation, seems to constitute an instrument which facilitates the students' reflection on work-practices. Even though several researchers have already studied the efficacy of HyperVideo, studies concerning the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The present contribution sought to encourage teachers to enhance their teaching resources by utilizing more technological platforms to enhance the delivery of lessons and the performance of students. Our findings confirm the benefit of the use of hyper video in education as observe by other researchers (Perini et al, 2019;Cattaneo et al, 2018;Cattaneo et al, 2016;Tiellet et al, 2010). Although the provided hyper video content was in addition to the typical teaching process, it was found to be of great interest to the students, who are more inspired to explore and play when interacting with technology, whether it be a video, text, or other kinds of interaction.…”
Section: Discussionsupporting
confidence: 89%
“…The present contribution sought to encourage teachers to enhance their teaching resources by utilizing more technological platforms to enhance the delivery of lessons and the performance of students. Our findings confirm the benefit of the use of hyper video in education as observe by other researchers (Perini et al, 2019;Cattaneo et al, 2018;Cattaneo et al, 2016;Tiellet et al, 2010). Although the provided hyper video content was in addition to the typical teaching process, it was found to be of great interest to the students, who are more inspired to explore and play when interacting with technology, whether it be a video, text, or other kinds of interaction.…”
Section: Discussionsupporting
confidence: 89%
“…In the first category, there was one study that evaluated the quantity of annotations (Mirriahi et al, 2018a) ). In the second category, three studies examined a reflective task which was accomplished using annotations (Perini et al, 2019;Leung & Shek, 2021;Shek, Leung, & To, 2021). Nilsson and Karlsson (2019) showed that a video analysis using annotations helped student teachers to focus their attention on specific aspects of their teaching and enabled reflection-on-action and decision making in their planning of future lessons.…”
Section: Implementation Of Video Annotations In the Examined Studiesmentioning
confidence: 99%
“…texts, photos and graphics) [42]. Video augmentation methods encompass different types of visual feedback, including video transcripts, concept maps, knowledge graphs and hypergraphs [5,6,27,33,36] that are specifically addressed in our project. Data driven investigations have explored possibilities for video augmentation through personalized fragment navigation [41], enhanced exploration of e-learning contents [28,34], automatic display of relevant frames and visual summaries representing points with high learner activity [20].…”
Section: Related Workmentioning
confidence: 99%
“…This study represents the first step of a project that aims to automate the extraction of concepts and relations from video sources and the subsequent provision of visual feedback and hypervideo services. The motivation is that, while video augmentation services have been shown to be useful for learners [30,33], they are hardly provided since their development is time-consuming and requires manual effort [39]. Specifically, in this paper we present two types of visual feedback -an augmented transcript and a dynamic concept map (map of concept's flow), and their evaluation, as methods to support video comprehension in the first-watch learning context.…”
mentioning
confidence: 99%